Comentando comentários: questões de texto, género e corpus - Gonçalves, Matilde; Carrilho, João (Revista da Associação Portuguesa de Linguística, 2020)
Based on the process of constituting a corpus on the practices of commentary, the aim of this paper is to discuss and exemplify some aspects related to the collection and organization of that corpus. In this way, it will be evident that a linear methodology - definition of a corpus, research method, elaboration of the database, cataloguing of the material collected, creation of a search engine - necessary for the study of the comment is a complex task that motivates reflection both on the constitution of a corpus and on the characteristics of genre and text, supported by a heuristic and case-based reasoning methodology.